Challenges for Institutions of Social Care Providing Services for Elder Persons and Attitude of the Staff to the Quality of Provided Services - Gečienė, Jolita; Gudžinskienė, Vida (Socialinė teorija, empirija, politika ir praktika, 2018)
[only abstract and keywords in English; full article, abstract and keywords in Lithuanian] In the article the quality of the social care services is analized in the context of the public services organization and evaluation, considering the aspects of the institutional care reorganization. The main challenges, that social care institutions working with elderly people face at the moment, are revealed. In 2017 the quantitative study was carried out in order to collect empirical data. The method of the research was a questionnaire. The quality of social services is assessed and the questionnaire was formed on the basics of EQUASS methodology. In order to collect empirical data in 2017 quantitative study was carried out. The SPSS data processing program is used to analyze the research data. The specific efficiency of quality indicators of social care institutions are calculated in accordance with the 10 qualitative principles of the EQUASS system: leadership, personnel, rights, ethics, partnership, participation, orientation to person, complexity, performance orientation and continuous improvement. Research Subjects: Employees of social welfare institutions providing long-term / short-term social care services for the elderly in Lithuania according to the list of occupations of employees in the field of social services (2014). The research involved 105 heads of institutions, 122 social workers, 36 employment specialists and 78 social work assistants working in social care institutions providing services for the elderly people. Results of the research: The research results revealed that, according to the subjective opinion of the research participants, the service quality level in social care institutions working with elderly people is rather high. The quality of social care home care services is mostly related to orientation to person, leadership, rights and ethics, and, to a lesser extent, to complexity, personnel, performance orientation, continuous improvement and participation, and the least to the partnership. Care homes employees of different positions similarly evaluate the overall quality, the response rates vary slightly. The vast majority of respondents indicate that social services provided in their care institutions are sufficient. A majority of respondents evaluate the general and special services very well and well. The analysis of the results of the research revealed that according the vast majority (85.6%)